1972
DOI: 10.1021/ja00779a020
|View full text |Cite
|
Sign up to set email alerts
|

Cesium tetrachlorocuprate. Structure, crystal forces, and charge distribution

Abstract: The crystal and molecular parameters of cesium tetrachlorocuprate have been refined using an X-ray diffraction intensity data set. The crystal system is orthorhombic, space group Pnam, with four formula weights per unit cell; the unit cell parameters are a = 9.7599 ( 12), b = 12.3967 (12), and c = 7.6091 (9) A. A total of 1786 independent reflections were used in least-squares refinement of the molecular parameters, leading to a final R factor (on F) of 5.5%. The anion has crystallographically imposed m symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…We find a systematic shift of the pressure scale which is needed to match the simulated and measured structures, similarly to other systems considered in this review . In the studied Cs 2 CuCl 4 system, this shift is approximately 1 GPa, since the optimized structure at 1 GPa reproduces the experimental structure at ambient pressure . One can argue then that the theoretical structures obtained at 1 GPa, 1.5 GPa, and 4.5 GPa provide good references for the measurements done at 0 GPa, 0.5 GPa, and 3.6 GPa, respectively.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…We find a systematic shift of the pressure scale which is needed to match the simulated and measured structures, similarly to other systems considered in this review . In the studied Cs 2 CuCl 4 system, this shift is approximately 1 GPa, since the optimized structure at 1 GPa reproduces the experimental structure at ambient pressure . One can argue then that the theoretical structures obtained at 1 GPa, 1.5 GPa, and 4.5 GPa provide good references for the measurements done at 0 GPa, 0.5 GPa, and 3.6 GPa, respectively.…”
Section: Resultssupporting
confidence: 69%
“…[8,40,86,101,102] In the studied Cs 2 CuCl 4 system, this shift is approximately 1 GPa, since the optimized structure at 1 GPa reproduces the experimental structure at ambient pressure. [155] One can argue then that the theoretical structures obtained at 1 GPa, 1.5 GPa, and 4.5 GPa provide good references for the measurements done at 0 GPa, 0.5 GPa, and 3.6 GPa, [1] respectively.…”
Section: Pressure Effectsmentioning
confidence: 97%
“…For the discussion of the magneto‐structural correlations in the compounds of Cs 2 CuCl 4− x Br x (0 ≤ x ≤ 2) it is useful to recall the results of structural investigations under pressure, so far available only for the x = 0 border compound. According to these X‐ray studies, performed up to 4.0 GPa, the structure stays orthorhombic, space group Pnma , up to 3.6 GPa with reduced lattice parameters compared to those at ambient pressure …”
Section: Magneto‐structural Correlationsmentioning
confidence: 98%
“…According to these X-ray studies, performed up to 4.0 GPa, [11] the structure stays orthorhombic, space group Pnma, up to 3.6 GPa with reduced lattice parameters compared to those at ambient pressure. [22][23][24] . At low pressures up to about 0.6 GPa, which is relevant for the present study, the changes in the lattice parameters were found to be linear with pressure.…”
Section: Magneto-structural Correlationsmentioning
confidence: 99%
See 1 more Smart Citation